Progress in edge plasma turbulence modelling—hierarchy of models from 2D transport application to 3D fluid simulations in realistic tokamak geometry. (13th October 2021) - Bufferand, H.; Bucalossi, J.; Ciraolo, G.; Falchetto, G.; Gallo, A.; Ghendrih, Ph.; Rivals, N.; Tamain, P.; Yang, H.; Giorgiani, G.; Schwander, F.; Scotto d'Abusco, M.; et al.
Abstract: This contribution presents the recent effort at CEA and French federation for fusion to simulate edge plasma transport with the new code SOLEDGE3X. The latter can be used both as a 2D transport code or as a 3D turbulence code. It makes possible simulating edge plasma up to the first wall including the complex wall geometry. It also includes neutral recycling and impurity sputtering, seeding and transport. In order to improve turbulence description in transport simulation, a reduced model for turbulence intensity prediction has been derived and implemented, based on ' k -epsilon' like models from the neutral fluid community. Applications to a JET L-mode detached plasma and to a WEST plasma are used as illustration of the code abilities.